Epidemiology and Resistance Profiles of Bacteria Isolated From Blood Samples in Septic Patients at Emergency Department Admission: A 6-Year Single Centre Retrospective Analysis From Northern Italy - Valeria Cento; Sara Carloni; Riccardo Sarti; Linda Bussini; Zian Asif; Paola Morelli; Francesco De Fazio; Federica Maria Tordato; Maddalena Casana; Debora Mondatore; Antonio Desai; Elena Generali; et al. (Journal of Global Antimicrobial Resistance)
Objective: This study aimed to investigate the microbiological and clinical heterogeneity of community-onset bloodstream infections (BSIs) and identify features to support targeted empirical antibiotic therapy in the Emergency Department (ED). Methods: Clinical and microbiological data from 992 BSI cases (1,135 isolates) diagnosed within 24 h of ED admission at IRCCS Humanitas Research Hospital, Milan, Italy (January 2015–June 2022), were analysed. Drug resistance was interpreted using EUCAST-2023. Clinical features included age, sex, comorbidities (e.g., cancer, diabetes), infection source, presence of central venous catheters (CVC), ongoing therapies, and sepsis severity. Microbiological data included pathogen identification and antimicrobial susceptibility. Results: Antibiotic-susceptible Escherichia coli (29.5%) was the most common isolate, including extended-spectrum beta-lactamase (ESBL)-producing strains (11.3%), followed by methicillin-susceptible Staphylococcus aureus (MSSA, 8.4%). BSIs due to E. coli were more frequent in patients >60 years (43.9% vs. 27.3%, P < 0.001) and associated with ESBL production (OR = 2.202, P = 0.031) and urosepsis (OR = 1.688, P = 0.006). Younger patients (≤60 years) had more S. aureus-associated BSIs (22.4% vs. 10.8%, P < 0.001) and methicillin resistance (7.9% vs. 3.6%, P = 0.021). Carbapenem-resistant Enterobacterales were rare (2.1%-2.8%), predominantly involving Klebsiella pneumoniae. Onco-hematological patients had a lower multidrug-resistance prevalence (9.5% vs. 21.1%, P < 0.001). Conclusions: Community-onset BSIs demonstrated substantial prevalence of resistant pathogens, including ESBL and MRSA, emphasizing the need for robust surveillance systems. Age is a critical factor in guiding empirical antibiotic therapy in the ED.